Pengaruh Kepemimpinan, Dan Motivasi Kepala Sekolah Terhadap Disiplin Kerja Guru Di SD Negeri Bual - Hadi, L. Asnan Kurnia Al; Ali, Muhamad; Parhanuddin, Lalu (Jurnal Ilmiah Global Education, 2025)
The purpose of this study was to determine whether or not there is an influence between the leadership and motivation of the principal on teacher work discipline at Bual Public Elementary School. The results of this study prove that the principal's leadership style, which includes managerial skills, decision-making, interpersonal relationships, conflict management, and change and innovation management, has a positive impact on teacher discipline. Furthermore, the motivation demonstrated by the principal, both intrinsic and extrinsic, also contributes to improving teacher discipline. When the principal shows appreciation, recognition, and support for teachers' work, teachers feel valued and motivated to demonstrate disciplined work performance.